Ameliorative Role of Green Tea and Zinc Oxide Nanoparticles Complex Against Monosodium Glutamate-Induced Testicular Toxicity in Male Rats - Hamza, Reham Z.; Al-Salmi, Fawziah A.; Laban, Hebatullah; El-Shenawy, Nahla S. (Current Pharmaceutical Biotechnology, 2020)
Background and Objective: This study was designed to estimate the long-term effects of zinc oxide nanoparticles/green tea (ZnONPs/GTE) complex against monosodium glutamate (MSG). The antioxidant/oxidative status, testosterone levels, DNA damage, and histopathological changes of testis were evaluated. Methods: The rats were divided into eight groups that were treated as follows: saline, the lower dosage of MSG (6.0 mg/kg), the higher dosage of MSG (17.5 mg/Kg), GTE, ZnONPs, ZnONPs/GTE and the last two groups were treated with the lower dosage of MSG or the higher dosage of MSG with ZnONPs/GTE complex. The data showed minimal toxicity in testicular tissue after the administration of ZnONPs. Results: The MSG treatment in the adult male rats reduced testosterone levels and disrupted testicular histology, which revealed dose-dependence of MSG. Also, ZnONPs induced testicular dysfunction through the interference of antioxidant/oxidant balance and suppression of testosterone levels as well as induction of cellular damage of testis. The combination of ZnONPs with GTE complex significantly protects against MSG or ZnONPs toxicity by decreasing the DNA damage, oxidative stress, and enhancement of antioxidant as well as histological structure of testis. Conclusion: We could recommend using ZnONPs/GTE complex to reduce the toxicity of ZnONPs and MSG on the testis at the cellular and oxidative stress levels.
Keywords: toxicity